m5C RNA methylation: a potential mechanism for infectious Alzheimer’s disease - Teng, Sisi; Han, Cunqiao; Zhou, Jian; He, Zhenyan; Qian, Weiwei (Frontiers in Cell and Developmental Biology, 2024)
Alzheimer's disease (AD) is a neurodegenerative disorder caused by a variety of factors, including age, genetic susceptibility, cardiovascular disease, traumatic brain injury, and environmental factors. The pathogenesis of AD is largely associated with the overproduction and accumulation of amyloid-β peptides and the hyperphosphorylation of tau protein in the brain. Recent studies have identified the presence of diverse pathogens, including viruses, bacteria, and parasites, in the tissues of AD patients, underscoring the critical role of central nervous system infections in inducing pathological changes associated with AD. Nevertheless, it remains unestablished about the specific mechanism by which infections lead to the occurrence of AD. As an important posttranscriptional RNA modification, RNA 5-methylcytosine (m 5 C) methylation regulates a wide range of biological processes, including RNA splicing, nuclear export, stability, and translation, therefore affecting cellular function. Moreover, it has been recently demonstrated that multiple pathogenic microbial infections are associated with the m 5 C methylation of the host. However, the role of m 5 C methylation in infectious AD is still uncertain. Therefore, this review discusses the mechanisms of pathogen-induced AD and summarizes research on the molecular mechanisms of m 5 C methylation in infectious AD, thereby providing new insight into exploring the mechanism underlying infectious AD.